Histopathological changes in autism using various histological staining techniques. - Subramaniam, Joshitha; Singh, Sanyuktha (Journal of Neonatal Surgery, 2024)
Introduction: Autism spectrum disorders (ASDs) are a cluster of related neurodevelopmental disorders characterized by varying degrees of impaired socialization, reduced communication, and limited, repetitive, or stereotyped interests and activities. The lack of a full understanding of the relationship between the brain and the behavior of autistic patients has hindered the development of effective methods for the diagnosis and management of autism. Various animal models have been employed to investigate the core symptoms, possible causes, and potential treatments of autism. Among the several animal models so far assayed, the rat model appears to be an excellent standard experimental system, predominantly because of the ample data already available on the genetics and behavioral phenotyping of various rat strains. Materials and Methods: 6 Wister rats are taken, 4 subjects are induced with autism 2 subjects are control Sacrificed Fixed in 10% formalin processed and staining done. Result and Discussion: In similar studies, several of the genetic models display some or all of the core behavioral features of autism. The animal work has not yet shed light on the mysterious strong male bias found in autism prevalence. Another frontier is represented by intriguing non-human primate models based on immune manipulation and maternal infection. Conclusion: We have observed hair sloughing, black discoloration of ruptured skin, and also coagulation necrosis by observing the epithelial tissues